Household Welfare of Rice-fish Farmers: An Income-Expenditure Ratio Approach - Triyono; Berliani Arifianikmah Ayu (E3S Web of Conferences)
The increase in agricultural land conversion activities can cause a decrease in rice productivity, while food demand is increasing. One of the alternatives that can be sought is land intensification through the rice-fish farming system. This study aims to determine the household income of farmers, household expenditures of farmers, and the welfare of households of rice mina farmers. The research was carried out in Candibinangun Village, which was determined by purposive, with a sample of 35 respondents taken by census. The analysis technique used is welfare analysis using the Good Service Ratio and the Farmer Household Income Exchange Rate, namely the household income-expenditure ratio. The results of the study show that the household income of rice-fish farmers, which is IDR 31,134,079, is greater than the household expenditure of farmers, which is IDR 22,078,686. With the contribution of mina rice farming to household income is 20.34%. Rice-fish farmer households in Candibinangun Village are categorized as prosperous based on welfare analysis using Good Service Ratio and FHIER. With a welfare value based on the Good Service Ratio of 0.98 and a welfare value based on the Farmer Household Income Exchange Rate of 1.41. However, these welfare indicators can be achieved by the contribution of income from activities outside the agricultural sector.